2018
DOI: 10.1002/cssc.201702001
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Polyimide/Graphene Composite Organic Cathodes for Fast and Sustainable Lithium‐Ion Batteries

Abstract: A composite organic cathode material based on aromatic polyimide (PI) and highly conductive graphene was prepared through a facile in situ polymerization method for application in lithium-ion batteries. The in situ polymerization generated intimate contact between PI and electronically conductive graphene, resulting in conductive composites with highly reversible redox reactions and good structure stability. The synergistic effect between PI and graphene enabled not only a high reversible capacity of 232.6 mAh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 54 publications
1
44
0
Order By: Relevance
“…[113] CNT and graphene were used as carriers, and polyimide was used as an active material. Small molecule carbon materials such as carbon black, SP, and KB can form dense networks, reduce pores, and increase the specific surface area for the reaction.…”
Section: Aromatic Polyimidesmentioning
confidence: 99%
“…[113] CNT and graphene were used as carriers, and polyimide was used as an active material. Small molecule carbon materials such as carbon black, SP, and KB can form dense networks, reduce pores, and increase the specific surface area for the reaction.…”
Section: Aromatic Polyimidesmentioning
confidence: 99%
“…One strategy is to prepare the composite material by combining the organic material with carbon matrix (carbon nanotubes, graphene materials, etc. ), which can effectively improve the electronic conductivity and cycle life . Another strategy is to design novel active organic frameworks with carefully crafted electronic structure and reversible multielectron redox capability …”
mentioning
confidence: 99%
“…These results demonstrate that PC has commendable thermal stability caused by the polymerization of catechol through the FeCl 3 initiator . Moreover, the mass losses of all the PC/G samples are lower than that of PC, which is attributed to the excellent thermal stability of graphene . Figure b shows the Fourier transform infrared (FTIR) spectra of the PC/G composites, pristine PC, and graphene.…”
Section: Resultsmentioning
confidence: 99%
“…Figure a reveals the CV curves of the graphene, PC, and PC/G samples. It is found that the electrochemically active area among the CV curves is largest for the PC/G‐2 sample, indicating a better zinc‐ion storage behavior of the PC/G‐2 cathode . Figure b illustrates the rate capacities of the PC/G composite cathodes and graphene.…”
Section: Resultsmentioning
confidence: 99%